2017
DOI: 10.18632/oncotarget.17488
|View full text |Cite
|
Sign up to set email alerts
|

Novel circular RNA expression profiles reflect progression of patients with hypopharyngeal squamous cell carcinoma

Abstract: Circular RNAs (circRNAs), a novel class of endogenous noncoding RNAs, have been shown to have important roles in a number of diseases, including several types of cancers. We hypothesized that circRNAs are involved in the pathogenesis of hypopharyngeal squamous cell carcinoma (HSCC). To test our hypothesis, we initially compared the expression profiles of circRNAs in 4 paired HSCC and adjacent normal tissue samples by using a circRNA microarray. The microarray data showed that 2392 circRNAs, including 1304 upre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…In recent years, circRNA-miRNA-gene regulatory axes were confirmed that involved in pathogenic processes or cancer [46,47]. In order to show a more intuitionistic result, three up-regulated circRNAs (chr5: 51521674-51524828-, chr3: 3137166-3138170+, chr4: 59505289-59510641-) in tumor liver samples of ALV-J-susceptible chickens were selected and five target miRNAs and 10 miRNA target genes were showed in the circRNA-miRNA-gene network which provides a foundation for further pathogenic mechanism research.…”
Section: Discussionmentioning
confidence: 98%
“…In recent years, circRNA-miRNA-gene regulatory axes were confirmed that involved in pathogenic processes or cancer [46,47]. In order to show a more intuitionistic result, three up-regulated circRNAs (chr5: 51521674-51524828-, chr3: 3137166-3138170+, chr4: 59505289-59510641-) in tumor liver samples of ALV-J-susceptible chickens were selected and five target miRNAs and 10 miRNA target genes were showed in the circRNA-miRNA-gene network which provides a foundation for further pathogenic mechanism research.…”
Section: Discussionmentioning
confidence: 98%
“…KEGG analysis showed that the MAPK signaling pathway and endocytosis were enriched for all 3 upregulated circRNAs. Meanwhile, the 3 downregulated circRNAs were involved in proteoglycans in cancer, choline metabolism in cancer, Wnt signaling pathway and AMPK signaling pathway [180]. Although the downstream miRNAs were estimated by the authors, the authentic functional mechanisms of altered cir-cRNAs need to be studied further in the future.…”
Section: Circrnas In Hypopharyngeal Squamous Cell Carcinoma (Hscc)mentioning
confidence: 97%
“…HSCC is one of the most aggressive HNCs. Microarray analysis showed 2392 dysregulated circRNAs in HSCC tissues compared with ANTs [180]. Among them, hsa_-circ_0058106, hsa_circ_0058107 and hsa_circ_0024108 were demonstrated to show higher expression, while hsa_circ_0036722, hsa_circ_0002260, and hsa_circ_ 0001189 showed lower expression in tumors than in ANTs.…”
Section: Circrnas In Hypopharyngeal Squamous Cell Carcinoma (Hscc)mentioning
confidence: 98%
“…These reports indicate that circRNAs may be emerging prognostic biomarkers and therapeutic targets in human cancers. In our previous study, we identified the different expression of circRNAs between HSCC tissues and adjacent normal tissues via microarray analysis. However, due to the limitation of microarray analysis, a large number of novel circRNAs beyond previous microarray analysis have yet to be identified.…”
Section: Introductionmentioning
confidence: 99%